Sensing voltage dynamics with differential intensity surface plasmon resonance system - Abayzeed, Sidahmed (2016)
The voltage sensitivity of surface plasmon resonance is investigated as a potential method for label-free detection of the dynamics of the transmembrane potential of excitable cells. Development of such a method for reliable detection of these signals is one of the modern challenges in biomedical research. Since they are key physiological signals that control a number of vital functions, they report the system's behaviour in health and disease. Labelling methods are currently used to detect these signals, often with subcellular resolution, but fluorescent labels (i) have a short lifetime, which limits the timescale of the experiments and (ii) they can be toxic to cells.